Pupulan Puisi Sangsiah Kélangan Somah Karya I Gdé Nala Antara Analisis Struktur - Nirmalasari, Ni Luh Dewi; Puspawati, Luh Putu; Suteja, I Wayan (Humanis; Vol 24 No 4 (2020), 2020)
This study is entitled “Pupulan Puisi Sangsiah Kélangan Somah Karya I Gdé Nala Antara Analisis Struktur”. Pupulan Puisi Sangsiah Kélangan Somah consists of four poems, namely poem Sangsiah Kélangan Somah, Tresna Uluh Kalarau, Pasah, and Semara Tan Patepi. Pupulan Puisi Sangsiah Kélangan Somah is analyzed by structural theory from Herman J. Waluyo. This study aims to describe the forming structures contained in the Pupulan Puisi Sangsiah Kélangan Somah in the form of physical structures and mental structures. Methods and techniques for providing research data using library and interview methods are supported by document, recording and note taking techniques. The methods and techniques of analyzing research data use descriptive analytic methods, and the hermeneutic method is assisted with translation and note taking techniques. The methods and techniques of presenting data analysis use formal and informal methods and are supported by deductive and inductive techniques. The structures that make up the Pupulan Puisi Sangsiah Kélangan Somah are divided into two, namely the physical structure (diction, imagination, concrete words, figurative speech or language, versification, and typography) and the mental structure (theme, taste, tone, and mandate).